ANALISIS OPENING AND CLOSING ACTIVITY DI FATHIMAH INTERNASIONAL ELEMENTARY SCHOLL TERHADAP MUATAN DIMENSI PROFIL LULUSAN - Ahmad Shiddiq; Ahmad Daifi; Taskiyatun Wildaniah; Muhammad Waqid; Uslifatul Jannah; Michael Nyoman Budiana Putra; Moh Ainor Rofiqi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the implementation of opening and closing activities and their contribution to the development of Graduate Profile dimensions at Fatimah International Elementary School. A descriptive approach was employed, with data collected through questionnaires administered to teachers and students. The findings reveal that the systematic and sustained implementation of these activities receives highly positive responses and significantly contributes to enhancing students’ learning readiness, discipline, and character formation. Furthermore, these practices support the development of key Graduate Profile dimensions, including citizenship, collaboration, communication, independence, creativity, critical thinking, and religiosity. These findings underscore the strategic role of integrated habituation practices within instructional activities in fostering holistic character education.